A multi-criteria decision-making framework for building sustainability assessment in Kazakhstan. (January 2020) - Akhanova, Gulzhanat; Nadeem, Abid; Kim, Jong R.; Azhar, Salman
Highlights: Step-wise assessment ratio analysis (SWARA) was used for weight allocation of building sustainability assessment system. A framework of Kazakhstan's building sustainability assessment was proposed. The proposed framework was compared with other international systems for validation. Abstract: Kazakhstan is the largest greenhouse gas emitter in Central Asia. The country has a significant renewable energy potential from solar, wind, hydro and biomass. Despite this, very small amounts of alternative energy sources have been used. Renewable sources such as wind, solar, small hydro and bioenergy currently contribute less than 1% of the country's energy mix. The building sector in Kazakhstan accounts for 30% of final energy consumption. In this regard, the role of the construction industry is extremely important due to its significant share in energy consumption and carbon emissions. This paper presents the results of the development of Kazakhstan's Building Sustainability Assessment framework. Stepwise weight assessment ratio analysis (SWARA) method was employed to calculate and allocate weights of assessment categories and indicators in the assessment framework. The reliability of the developed framework was validated by comparing its performance sensitivity with fours rating systems, namely, BREEAM, LEED, CASBEE, and SBTool for the categories of the proposed framework. The output of the research can produce a useful reference to the green building policymakers in the country. Also, the proposed framework can be adapted for use in Kazakhstan's neighboring countries which share similar climatic zones and conditions.